2016
DOI: 10.1089/neu.2015.3949
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Brain-Derived Neurotrophic Factor Has Diagnostic and Prognostic Value in Traumatic Brain Injury

Abstract: Brain-derived neurotrophic factor (BDNF) is important for neuronal survival and regeneration. We investigated the diagnostic and prognostic values of serum BDNF in traumatic brain injury (TBI). We examined serum BDNF in two independent cohorts of TBI cases presenting to the emergency departments (EDs) of the Johns Hopkins Hospital ( JHH; n = 76) and San Francisco General Hospital (SFGH, n = 80), and a control group of JHH ED patients without TBI (n = 150). Findings were subsequently validated in the prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 71 publications
5
88
1
Order By: Relevance
“…Simon et al, 2016 reported no predictive value for BDNF to discriminate survival and nonsurvival patients 37. Similar to our findings, day‐of‐injury serum BDNF was associated with TBI diagnosis; however, the authors also showed 6‐month prognostic value regarding recovery from TBI 38. Further, the CSF levels of BDNF predicted mortality within 7 days of hospitalization after severe TBI 39.…”
Section: Discussionsupporting
confidence: 81%
“…Simon et al, 2016 reported no predictive value for BDNF to discriminate survival and nonsurvival patients 37. Similar to our findings, day‐of‐injury serum BDNF was associated with TBI diagnosis; however, the authors also showed 6‐month prognostic value regarding recovery from TBI 38. Further, the CSF levels of BDNF predicted mortality within 7 days of hospitalization after severe TBI 39.…”
Section: Discussionsupporting
confidence: 81%
“…Future investigation will examine how biomarkers correlate with functional changes observed on imaging and behavioral changes detected on exam. Korley and colleagues found significant serum changes of brain-derived neurotrophic factor in children with functional imaging changes following TBI indicating increased susceptibility for depression [107]. Further studies are necessary to determine if sensory processing deficits are linked to changes in mood.…”
Section: Advanced Imaging Correlationsmentioning
confidence: 99%
“…This finding adds to other literature in the field that drops in BDNF may serve as a viable biomarker of concussion. For example, Korley et al (2016) found that BDNF levels were significantly lower in mild TBI cases compared to moderate and severe TBI when assessed on the day of the injury. Additionally, they reported that lower BDNF levels following mTBI was predictive of poorer outcomes at a 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%